PENGEMBANGAN ALAT BANTU LATIHAN SHOOTING FREE THROW MENGGUNAKAN PORTABLE MISTAR SHOOT DALAM PERMAINAN BOLA BASKET - Kolbi, Muhammad Khaniful (Universitas Negeri Semarang, 2021)
The imbalance between the shooting skills training process in the field. Slows down mastery ofindividual shooting abilities. The aim of this research is: (1) Develops shooting practiceshooting. (2) Knowing the feasibility of the Portable Ruler Shoot tool according to the validatorfilling. The method used in this research is research and development methods. The data usedin this research are qualitative and quantitative data. Qualitative data is generated from expertadvice and input. Quantitative results are obtained from filling out questionnaires submitted toexperts and samples in small and large group trials. The results of the development researchcarried out will get: (1) The results of expert validation get a percentage of 79.58%, good andworthy. (2) The results of small-scale trial data get a percentage of 72%, good and worthy. (3)The results of the large scale data trial obtained a percentage of 90.68%, good and worthy. so isdeclared valid and worthy.